Expression of a synthetic gene encoding the enhanced green fluorescent protein in various Escherichia coli strains - Nha Trang, Nguyen Thi; Thu Ha, Huynh Thi; Phuong Thao, Nguyen; Anh Tho, Duong Thi; Trang, Cao Thi; Ha Thanh, Le Thi; Hoang Tue, Nguyen; Hoang Loc, Nguyen; Ngoc Luong, Nguyen (Vietnam Journal of Biotechnology, 2022)
Enhanced Green Fluorescent Protein (eGFP) shows much stronger fluorescence than its ancestor, Green Fluorescent Protein (GFP), thus has been widely applied as a reporter for biomedical research. In this study, we reported the expression of a synthetic codon optimized gene encoding eGFP in Escherichia coli (E. coli). The gene was cloned into two expression vectors, pQE30 and pColdII and the resulting recombinant vectors were transformed into E. coli M15 and BL21 De3 RIL codon plus strains, respectively. The expression levels of functional eGFP showed a temperature dependent pattern, in which lowering the induction temperature increased the amount of functional eGFP. Surprisingly, eGFP showed a phenomenon called auto-induction when E. coli TOP10 cells carrying recombinant pQE30 and pColdII were grown on Luria Broth plates. The recombinant eGFP showed robust stability even at room temperature, thus greatly facilitated its purification and handling. Mouse polyclonal antibodies were conveniently generated against the protein. Besides its potential application as a reporter gene in E. coli, the gene and its expression systems reported here are extremely useful as models for teaching recombinant DNA technology at undergraduate level.